Population growth and environmental resources: A short note on their relationships and consequences and impacts - Yap, Chee Kong; Rosimah Nulit; Wan Mohd Syazwan; Hishamudin Omar; Kennedy Aaron Aguol; Munir Mohd Nawi (Biomedical Research Network, 2024)
Resources and the environment are significantly impacted by population increase. This study aimed to analyse the literature on population growth and the environment and create a qualitative information synthesis concerning the well-known common effects of environmental pressures brought on by population expansion. The following five results can be interpreted as an increase in the human population based on the complete body of literature retrieved from the Scopus database. First and foremost, resource consumption is rising; second, habitat loss and biodiversity loss; third, the environmental stresses due to human activities on ecosystems; fourth, increased waste output; and fifth, expedited climate change is worsening due to the continuous rise in greenhouse gas emissions. The increase in energy consumption, food demands, transportation needs, and industrial activity are the main contributors to the aforementioned factors.